Pengaruh Sales Promotion Dan Hedonic Shopping Motivation Terhadap Impulsive Buying Melalui Positive Emotion Sebagai Variabel Intervening (Studi Pada Pelanggan Tokopedia di Kota Cilegon) - Izzuddin, Zaki Muhammad Zain; Damarwulan, Liza Mumtazah; Setya, Yanto Azie (Universitas Sultan Ageng Tirtayasa, 2025)
The purpose of this study was to determine the Influence of Sales Promotion and Hedonic Shopping Motivation on Impulsive Buying Through Positive Emotion as an Intervening Variable of the Study on Tokopedia Customers in Cilegon City. This study uses a quantitative method with a purposive sampling type of 170 respondents. The data analysis technique for this study uses Structural Equation Modeling (SEM) using the Partial Least Square (SmartPLS) version 4.0 program tool. The results of this study indicate that: (1) Sales Promotion has no effect on Impulsive Buying. (2) Hedonic Shopping Motivation has a positive and significant effect on Impulsive Buying. (3) Sales Promotion has a positive and significant effect on Positive Emotion. (4) Hedonic Shopping Motivation has a positive and significant effect on Positive Emotion. (5) Positive Emotion has a positive and significant effect on Impulsive Buying. (6) Positive Emotion is able to mediate the influence of Sales Promotion and Hedonic Shopping Motivation on Impulsive Buying.